The willingness of people who inject drugs in Boston to use a supervised injection facility. Issue 1 (2nd January 2018) - León, Casey; Cardoso, Lena; Mackin, Sarah; Bock, Barry; Gaeta, Jessie M.
ABSTRACT: Background : In Massachusetts, the number of opioid-related deaths has increased 350% since 2000. In the setting of increasing overdose deaths, one potential intervention is supervised injection facilities (SIFs). This study explores willingness of people who inject drugs in Boston to use a SIF and examines factors associated with willingness. Methods : A cross-sectional survey of a convenience sample of 237 people who inject drugs and utilize Boston's needle exchange program (NEP). The drop-in NEP provides myriad harm reduction services and referrals to addiction treatment. The survey was mostly self-administered (92%). Results : Results showed positive willingness to use a SIF was independently associated with use of heroin as main substance (odds ratio [OR]: 5.47; 95% confidence interval [CI]: 1.9–15.4; P = .0004), public injection (OR: 5.09; 95% CI: 1.8–14.3; P = .002), history of seeking substance use disorder (SUD) treatment (OR: 4.99; 95% CI: 1.2–21.1; P = .05), having heard of SIF (OR: 4.80; 95% CI: 1.6–14.8; P = .004), Hispanic ethnicity (OR: 4.22; 95% CI: 0.9–18.8; P = .04), frequent NEP use (OR: 4.18; 95% CI: 1.2–14.7; P = .02), current desire for SUD treatment (OR: 4.15; 95% CI: 1.2–14.7; P = .03), hepatitis C diagnosis (OR: 3.68; 95% CI: 1.2–10.1; P = .02), posttraumatic stress disorder (PTSD) diagnosis (OR: 3.27; 95% CI: 1.3–8.4; P = .01), report of at least 1 chronic medical diagnosis (hepatitis C, human immunodeficiency virus [HIV], hypertension, or diabetes) (OR: 3.27; 95% CI: 1.2–8.9; P = .02), and comorbid medical and mental health diagnoses (OR: 2.93; 95% CI: 1.2–7.4; P = .02). Conclusions : Most respondents (91.4%) reported willingness to use a SIF. Respondents with substance use behavior reflecting high risk for overdose were significantly more likely to be willing to use a SIF. Respondents with behaviors that contribute to public health burden of injection drug use were also significantly more likely to be willing to use a SIF. Results indicate that this intervention would be well utilized by individuals who could most benefit from the model. As part of a broader public health approach, SIFs should be considered to reduce opioid overdose mortality, decrease public health burden of the opioid crisis, and promote access to addiction treatment and medical care.